Effect of Oxygen Impurity on Thermal Conduction Rate of Polycrystalline Si3N4. Issue 10 (21st October 2021) - Dow, Hwan Soo; Na, Moonkyong; Jung, Yeon Wook; Geun Jo, Seung; Lee, Jung Woo
Abstract : Heat transfer with homogeneous structures of Si3N4 system and the effects of oxygen defects in the Si3N4 grains are reported by Jung Woo Lee and co‐workers in article number 2100566 . The oxygen defects in the grains are moving to the surface of the grains and effectively captured by oxygen getter. The inhibition of the Si3N4 grain oxidization improves a spontaneous dissipation of thermal energy.